Marriage stability in a pastoralist society. (8th July 2019) - Du, Juan; Mace, Ruth
Abstract: We examined how individual investment was associated with the duration of marriage partnerships in a pastoralist society of Amdo Tibetans in China. We collected demographic and socioeconomic data from 420 women and 369 men over five villages to assess which factors predicted partnership length. We found that the payment of dowry and bridewealth from both sides of the family predicted marriage stability. The production of offspring, regardless of their survivorship, also had a positive effect on marriage duration, as did trial marriage, a time period before formal marriage. Finally, we found that if both bride and groom invest resources initially into a partnership—whether wealth or labor—their subsequent partnership is stronger than couples who do not make such investments. This paper adds to our understanding of complex social institutions like marriage from a behavioral ecological perspective. Abstract : Choosing a long-term partner is literally a life-changing decision. Here, using data from Tibetan pastoralists, we found that a trial marriage, which gives both parties the opportunity to assess the other's quality, resulted in more stable marriages. The qualities assessed include female labor ability before marriage, brideprice payment at marriage, and fertility after the marriage. We also found that if either or both sides of the partnership invested wealth into the marriage, the duration of the marriage was longer than when partners did not make such contributions.